The transcription factor BATF operates as an essential differentiation checkpoint in early effector CD8+ T cells - Kurachi, Makoto; Barnitz, R Anthony; Yosef, Nir; Odorizzi, Pamela M; DiIorio, Michael A; Lemieux, Madeleine E; Yates, Kathleen; Godec, Jernej; Klatt, Martin G; Regev, Aviv; Wherry, E John; Haining, W Nicholas (Nature immunology, 2014)
The transcription factor BATF is required for differentiation of certain helper T cell subsets. Haining and colleagues show that BATF crucially regulates CD8 + effector cells by coordinating a transcription factor network. The transcription factor BATF is required for the differentiation of interleukin 17 (IL-17)-producing helper T cells (T H 17 cells) and follicular helper T cells (T FH cells). Here we identified a fundamental role for BATF in regulating the differentiation of effector of CD8 + T cells. BATF-deficient CD8 + T cells showed profound defects in effector population expansion and underwent proliferative and metabolic catastrophe early after encountering antigen. BATF, together with the transcription factors IRF4 and Jun proteins, bound to and promoted early expression of genes encoding lineage-specific transcription-factors (T-bet and Blimp-1) and cytokine receptors while paradoxically repressing genes encoding effector molecules (IFN-γ and granzyme B). Thus, BATF amplifies T cell antigen receptor (TCR)-dependent expression of transcription factors and augments the propagation of inflammatory signals but restrains the expression of genes encoding effector molecules. This checkpoint prevents irreversible commitment to an effector fate until a critical threshold of downstream transcriptional activity has been achieved.